Coexistence of pachyonychia congenita and hidradenitis suppurativa: more than a coincidence. (17th June 2022) - Pavlovsky, Mor; Peled, Alon; Sarig, Ofer; Astman, Nadav; Malki, Liron; Meijers, Odile; Assaf, Sari; Schwartz, Janice; Malovitski, Kiril; Hansen, David; Sprecher, Eli; Samuelov, Liat
Abstract: Background: The coexistence of pachyonychia congenita (PC) and hidradenitis suppurativa (HS) has been described in case reports. However, the pathomechanism underlying this association and its true prevalence are unknown. Objectives: To determine the genetic defect underlying the coexistence of PC and HS in a large kindred, to delineate a pathophysiological signalling defect jointly leading to both phenotypes, and to estimate the prevalence of HS in PC. Methods: We used direct sequencing and a NOTCH luciferase reporter assay to characterize the pathophysiological basis of the familial coexistence of HS and PC. A questionnaire was distributed to patients with PC registered with the International Pachyonychia Congenita Research Registry (IPCRR) to assess the prevalence of HS among patients with PC. Results: Direct sequencing of DNA samples obtained from family members displaying both PC and HS demonstrated a missense variant (c.275A>G) in KRT17, encoding keratin 17. Abnormal NOTCH signalling has been suggested to contribute to HS pathogenesis. Accordingly, the KRT17 c.275A>G variant resulted in a significant decrease in NOTCH activity. To ascertain the clinical importance of the association of HS with PC, we distributed a questionnaire to all patients with PC registered with the IPCRR. Seventy‐two of 278 responders reported HS‐associated clinical features (25·9%) . Disease‐causing mutations in KRT17 were most prevalent among patients with a dual phenotype of PC and HS (43%). Conclusions: The coexistence of HS and KRT17 ‐associated PC is more common than previously thought. Impaired NOTCH signalling as a result of KRT17 mutations may predispose patients with PC to HS. What is already known about this topic? The coexistence of pachyonychia congenita (PC) and hidradenitis suppurativa (HS) has been described in case reports. However, the pathomechanism underlying this association and its true prevalence are unknown. What does this study add? A dual phenotype consisting of PC and HS was found to be associated with a pathogenic variant in KRT17 . This variant was found to affect NOTCH signalling, which has been previously implicated in HS pathogenesis. HS was found to be associated with PC in a large cohort of patients with PC, especially in patients carrying KRT17 variants, suggesting that KRT17 variants causing PC may also predispose to HS. What is the translational message? These findings suggest that patients with PC have a higher prevalence of HS than previously thought, and hence physicians should have a higher level of suspicion of HS diagnosis in patients with PC. Abstract : The co‐existence of pachyonychia congenita (PC) and hidradenitis suppurativa (HS) has been described in case reports. However, the pathomechanism underlying this association and its true prevalence are unknown. We used direct sequencing and a NOTCH luciferase reporter assay to characterize the pathophysiological basis of the familial co‐existence of HS and PC. A questionnaire was distributed to PC patients registered with the International PC Research Registry (IPCRR) to assess the prevalence of HS among PC patients. A dual phenotype consisting of PC and HS was found to be associated with a pathogenic variant in KRT17. This variant was found to affect NOTCH signaling which has been previously implicated in HS pathogenesis. HS was found to be associated with PC in a large cohort of PC patients, especially in patients carrying KRT17 variants, suggesting that KRT17 variants causing PC may also predispose to HS.